PUSHING THE BOUNDARIES : STORIES FROM THE PUTRAJAYA YEARS (MAY 2000 - MAY 2013) - Nor Mohamed Yakcop Tan Sri, Dato' , 1947- (MPH Group Publishing Sdn Bhd, 2016)
Inside this fascinating book are many true stories of tribulations and triumphs, written by some 27 individuals, most of them thought-provoking, many of them touching and a few of them funny, but all of them attempt to provide an insight into the developmental activities in Malaysia between May 2000 and May 2013, an important period of Malaysia's recent history.